(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The Colleges of Santa Cruz and San Gregorio have been two emblematic institutions at the University of Valladolid. Founded in the reign of the Catholic Monarchs by two powerful ecclesiastics who located their institutions in magnificent buildings that have endured over time. Its function as a collegiate center ended with the suspension of this type of institution and the buildings were used for other purposes. Currently the Santa Cruz Palace is used as university premises and headquarters of the Rectorate of the University of Valladolid and the San Gregorio Palace as a Museum. Both institutions have had a rich history full of events and anecdotes in their more than four hundred years of history.